2016
DOI: 10.1016/j.aca.2016.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared spectroscopic imaging assessment of cartilage composition: Validation with mid infrared imaging spectroscopy

Abstract: Disease or injury to articular cartilage results in loss of extracellular matrix components which can lead to the development of osteoarthritis (OA). To better understand the process of disease development, there is a need for evaluation of changes in cartilage composition without the requirement of extensive sample preparation. Near infrared (NIR) spectroscopy is a chemical investigative technique based on molecular vibrations that is increasingly used as an assessment tool for studying cartilage composition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…Utilization of 80 μm sections is unconventional in the MIR range, because the depth of penetration of the IR radiation is typically only several micrometers. However, this is also dependent on the specific absorptivity coefficient of the vibration being studied, as shown by a previous study in our laboratory where the effects of various sample thicknesses on the signal‐to‐noise ratio and linearity of absorbance was assessed . Data showed that the absorbance of amide I and II bands reached saturation due to attenuation of the signal, but the MIR bands at 856 and 1340 cm –1 , which have substantially smaller absorptivity coefficients, and all of the NIR bands did not reach saturation.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Utilization of 80 μm sections is unconventional in the MIR range, because the depth of penetration of the IR radiation is typically only several micrometers. However, this is also dependent on the specific absorptivity coefficient of the vibration being studied, as shown by a previous study in our laboratory where the effects of various sample thicknesses on the signal‐to‐noise ratio and linearity of absorbance was assessed . Data showed that the absorbance of amide I and II bands reached saturation due to attenuation of the signal, but the MIR bands at 856 and 1340 cm –1 , which have substantially smaller absorptivity coefficients, and all of the NIR bands did not reach saturation.…”
Section: Discussionmentioning
confidence: 65%
“…The absorbance seen in the MIR spectra at ∼856 cm –1 arises from the C–O–S vibrations of the sGAG chains. The intensity of this peak is directly correlated with the content of PG in cartilage, and it has been used previously to quantify the spatial distribution of PG in engineered cartilage . sGAGs are glycosylated proteins and make up 10–15% of the wet weight of articular cartilage .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The absorption bands in the NIR region are overtones and combinations of the MIR fundamental vibrations of C–H, C–O, O–H and N–H bonds and are therefore appropriate for monitoring water, lipids, proteins and sugars. The main components of the cartilage ECM— water, collagen, and chondroitin sulfate (from proteoglycan) — have been identified and quantified using NIR spectroscopy with strong correlations to gold standard methods 7375 . Palukuru et al 74 ascribed the peaks at 4050, 4260, 4610 and 4890 cm −1 to collagen, the peaks at 4020 and 4310 cm −1 to the sugar component of proteoglycans, and the peak at 4350–4375 cm −1 to chondroitin sulfate.…”
Section: Applications Of Fourier Transform Infrared Spectroscopy Anmentioning
confidence: 99%